SELECTED PARAMETERS OF CHRONIC SOCIAL STRESS IN OPEN POPULATION — ASSOCIATION WITH THE PREVALENCE OF ISCHEMIC HEART DISEASE - E. V. Akimova; V. Yu. Smaznov; M. M. Kayumova; E. I. Gakova; A. M. Akimov; V. V. Gafarov; V. A. Kuznetsov (Кардиоваскулярная терапия и профилактика)
Aim. To study the parameters of stress at work in men 25-64 years old in open population and their association with the prevalence of ischemic heart disease (CHD).Material and methods. The study conducted on representative selection, created using election lists of males 25-64 y.o. from one of the districts of Tyumen city. In the frames of cardiological screening the prevalence of CHD in population and also the stress at workplace were studied using standard WHO questionnaire MONICA-psychosocial.Results. In open population of 25-64 y.o. in Tyumen in 85,9% of men there were significant changes at workplace during previous 12 months, in 4,0% — 41,2% of population there were other types of stress at workplace.Conclusion. While having certain CHD types and CHD by enhanced epidemiologic criteria it was shown that there is a decrease of responsibility and load at workplace, growth of negativity in relations to the occupation.